Knowledge Level of Parents, Teachers, and Students of SD Taman Harapan Islam Medan About Covid-19 Pandemic Prevention - Yanti, Nevi; Batubara, Fitri Yunita; Octiara, Essie; Siregar, Darmayanti (Talenta Publisher, 2021)
The new corona virus epidemic (COVID-19) was declared a global pandemic on March 11, 2020 by the World Health Organization (WHO). The Covid-19 mortality rate in Indonesia of 8.9% is the highest number in Southeast Asia. Knowledge of the prevention of the Covid-19 pandemic is very important to prevent the transmission of Covid-19. The purpose of this study was to determine the level of knowledge of parents, teachers, and students of Taman Harapan Islam Medan Elementary School about the prevention of the Covid-19 pandemic. This study used a pretest questionnaire for initial data collection, then counseling was carried out on the prevention of Covid-19 and for the final data collection, a postest questionnaire was used. The results of the Mann Whitney test showed that there were differences in the level of knowledge of parents and children about Covid-19 before counseling (p: 0.022) and there were differences in the level of knowledge of parents and children about Covid-19 after counseling (p: 0.002). So it can be concluded that there is an influence on the level of knowledge of parents and children about the spread of Covid-19 infection. Education about preventing the spread of Covid-19 to parents of students, teachers and students of the Taman Harapan Islam Medan Elementary School can provide an understanding of the importance of preventing the spread of Covid-19 and can be passed on to their families and the surrounding environment.